The professional knowledge and ability of the coach in the regulation of body weight in wrestlers - Shevtsov, A.; Krikuha, Y. (International Journal of Wrestling Science, 2011)
Study of the practice of combat sports has shown that athletes wishing to be stronger than their opponents, in one degree or another attempt to decrease their body weight (except for wrestlers heavy-weight categories). This decrease in body weight, beginning with participation in the first competition, has almost become a mandatory attribute of wrestling. This fact leads to the point that almost all the wrestlers and coaches have their own opinions about how quickly and without a loss in sports fitness should one drop those extra pounds in the competitive season. These opinions and practices are not always aligned with scientific approaches to weight reduction in wrestlers. Decrease in body weight is transferred and the young wrestlers, damaging their health and development of a growing organism. In the literature there are extensive presentations on the results of scientific research into various means and ways to reduce the weight of the wrestlers. In this case, as a rule, the researchers argue that they have developed a way to weight loss is the best and most effective, forgetting that weight loss is time consuming and complicated, and most importantly, an individual process that depends on several factors (socio-economic, psychological and physiological). Therefore, the only professionally competent coach who possesses the necessary knowledge and skills, a set of science-based technologies, as well as an awareness of his pupil, may help him in the individual selection of a specific process for the reduction of body weight. Only in this context can we understand the totality of knowledge about the ways and means of reduction of body weight. The integration of theoretical and empirical scientific knowledge and methods to combat allowed us to identify ways and identify the main and auxiliary means of reducing body weight, wrestlers used in the process of reducing body weight in preparation for the competition, and develop technologies to reduce weight: forced, shock, uniform, gradually increasing, interval-a lot of impact, wavy.